2020
DOI: 10.1159/000505246
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Interrelationship between Education, Income, and Obesity among Adults in Saudi Arabia

Abstract: <b><i>Objective:</i></b> To examine the association of sociodemographic variables with the odds of being obese among adults in Saudi Arabia, and to examine whether or not the association between the educational level and the odds of being obese among adults in Saudi Arabia is modified by the income level. <b><i>Methods:</i></b> A total of 3,925 participants were recruited for this cross-­sectional study. Sociodemographic and anthropometric data were collected usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
5
24
0
Order By: Relevance
“…The findings on the association between income and obesity are conflicting, which again may represent a nonlinear “u‐shaped” association or differences in study design. In four cross‐sectional studies ( n = 28,065), the prevalence of obesity was highest among high‐income participants, 13,17,34,37 whereas in two other studies ( n = 660), the prevalence of obesity was highest among the low‐income group 29,35 …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The findings on the association between income and obesity are conflicting, which again may represent a nonlinear “u‐shaped” association or differences in study design. In four cross‐sectional studies ( n = 28,065), the prevalence of obesity was highest among high‐income participants, 13,17,34,37 whereas in two other studies ( n = 660), the prevalence of obesity was highest among the low‐income group 29,35 …”
Section: Resultsmentioning
confidence: 94%
“…Of note, in a cross‐sectional study with over 3000 participants, the relationship between educational level and obesity based on income was explored; in the high‐income group, the odds of obesity among those with only middle or high school education was 2.15 (95% CI: 1.48–3.11) compared with 1.24 (95% CI: 1.01–1.50) in those with a college degree or higher. Further, participants with an elementary school education level were 2.12 (95% CI: 1.32–3.39) times more likely to have obesity in the low‐income group compared with 4.29 (95% CI: 2.35–7.84) in the higher income group 34 …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A variety of studies addressed the topic of obesity and its causes, which provided statistical data that show its prevalence and the associated factors. Among these studies is a study by Mosli et al [ 5 ], which discovered the association between educational level and income level with odds of being obese among adults in KSA. In contrast to participants with advanced education or higher, ignorant participants and those with rudimentary schooling had higher chances of corpulence.…”
Section: Introductionmentioning
confidence: 99%
“…In a later study, the overall prevalence of overweight and obesity among adults visiting primary care settings in the Southwestern Region of Saudi Arabia was found to be 38.3 and 27.6%, respectively [ 30 ]. Mosli et al [ 31 ] observed that individuals in the highest income bracket with lower levels of education have greater odds of obesity. The prevalence of obesity among adults in Saudi Arabia increased from 22% in 1990–1993 to 36% in 2005, and future projections of the prevalence of adult obesity in 2022 was estimated to be 41% in men and 78% in women [ 32 ].…”
Section: Discussionmentioning
confidence: 99%